2016
DOI: 10.12659/pjr.897304
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Doses and Image Quality in Mammography with Screen-Film, CR, and DR Detectors – Application of the ACR Phantom

Abstract: SummaryBackgroundDifferent methods of image quality evaluation are routinely used for analogue and digital mammography systems in Poland. In the present study, image quality for several screen-film (SF), computed radiography (CR), and fully digital (DR) mammography systems was compared directly with the use of the ACR mammography accreditation phantom.Material/MethodsImage quality and mean glandular doses were measured and compared for 47 mammography systems in the Mazovia Voivodeship in Poland, including 26 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…[ 13 ] The previous studies have shown that a fully digital mammography (FDM) system has optimum image quality and is capable of detecting subtle calcification clusters with low dose. [ 14 , 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] The previous studies have shown that a fully digital mammography (FDM) system has optimum image quality and is capable of detecting subtle calcification clusters with low dose. [ 14 , 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…Mammographic image quality and MGD depend on imaging technique and the radiographic system used. The patient radiation dose per mammographic examination is lower compared to the previous published researches (Warren et al, 2016, Pasicz et al, 2016, Fartaria et al, 2016, Ślusarczyk-Kacprzyk et al, 2016, Soliman and Bakkari, 2015, Hauge et al, 2014, Al-Kafi et al, 2009, Dance et al, 2009, Smathers et al, 2007, Kruger and Schueler, 2001) (Fig. 2).…”
Section: Discussionmentioning
confidence: 56%
“…However, to diminish the risk of radiation induced malignant tumors, precise patient dose estimation and optimization are required to bring down the probability of breast cancer to its minimal value (EC, 1996). In the literature, the mean glandular dose (MGD) ranged between 2.0 and 3.7 mGy per procedure (Warren et al, 2016, Pasicz et al, 2016, Fartaria et al, 2016, Ślusarczyk-Kacprzyk et al, 2016, Soliman and Bakkari, 2015, Hauge et al, 2014, Al-Kafi et al, 2009). Although, evaluation of patients' ionizing radiation exposures from radiodiagnostic examinations is recommended for dose optimization and benefit/risk evaluation, few studies have been published regarding patient doses during mammography in Saudi Arabia (Soliman and Bakkari, 2015, Al-Kafi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Regular quality control is required by law in Poland for those methods of medical imaging which involve the use of ionizing radiation [ 17 , 18 ]. Despite a rising number of ultrasound scanners and examinations, systematic quality control of ultrasound equipment is not required.…”
Section: Introductionmentioning
confidence: 99%